The role of decentralization in public administration - Chepelenko, Khrystyna (Запоріжжя: НБ ТДАТУ, 2025)
Decentralization has long been recognized as a crucial element in the promotion of good governance, public administration efficiency, and democratic participation. It encompasses a range of processes, including political devolution, de-concentration, delegation, and the transfer of responsibilities to non-governmental organizations. By bringing decision-making closer to the people, decentralization fosters stronger institutional frameworks, enhances citizen participation, and builds partnerships among various stakeholders.
Keywords: decentralization; political decentralization; administrative decentralization; central governments